PUBLIC RELATIONS AND PROMOTION OF ECOTOURISM IN CÔTE D'IVOIRE: Analysis of OIPR's awareness-raising mechanisms - (:unkn) unknown (My University, 2019)
This prose proposes to analyze the contribution of Public Relations to the positioning of the image of Ivorian protected areas as reference destinations for ecotourism in Africa. Indeed, like many African countries, Côte d'Ivoire has a vast natural and cultural potential that predisposes it to the practice of ecotourism. However, the dissuasive image of protected areas and the erosion of the capital of trust of eco-customers caused respectively by deforestation and the political instability of the country as well as the lack of information on tourist potential are the main factors that inhibit the development of ecotourism. In order to rebuild image capital, trust and make green tourism a lever for conservation and local development, the State carries out numerous public relations actions through its technical body, the OIPR. The research posture adopted in this thesis therefore seeks to know: “What is the contribution of public relations in the promotion of ecotourism in Côte d’Ivoire? To answer this question, action research was necessary. As a method of data collection, both qualitative and quantitative approaches were used. The main results obtained show that the use of public relations makes it possible to increase the attractiveness of protected areas, to establish trust with eco-customers, to involve stakeholders in the promotion of protected areas and to establish a symmetrical two-way communication with them. Faced with the limits of the communications actions carried out, the work proposes a public relations strategy based on the R.A.C.E method with a view to instilling the development of green tourism.
Keywords: African Research